Imago Dei and Artificial Intelligence Hardware as a Theological Evaluation of Human Agency in Autonomous Systems - Benefit Semuel Narasiang; Riandli Saliareng (Peneliti.net, 2026)
The rapid advancement of artificial intelligence (AI) hardware has enabled autonomous systems to make life-and-death decisions without direct human intervention. From self-driving vehicles that navigate urban streets to military drones equipped with lethal autonomous capabilities, and surveillance systems that algorithmically profile individuals, AI has transcended its origins as mere software to become embedded in silicon chips, sensors, and embedded systems. This phenomenon raises profound theological questions: When machines make decisions affecting human life, does human moral agency remain intact? How should the concept of Imago Dei (the image of God) be understood when electronic systems process decisions of life and death? This article employs a systematic theological-normative methodology, integrating hermeneutical analysis of biblical texts (Genesis 1:26-27, Psalm 8, Colossians 1:15), doctrinal synthesis from patristic to contemporary theology (Irenaeus, Augustine, Barth, Pannenberg, Zizioulas), and empirical data from autonomous vehicle incidents, military AI applications, and surveillance technologies. The findings demonstrate that between July 2021 and November 2025, autonomous vehicles were involved in 5,202 reported incidents in the United States alone, resulting in 451 injuries and fatalities, while military AI systems have raised critical concerns regarding meaningful human control and moral accountability. Theologically, this article argues that human moral agency remains irreducible to algorithmic processes, grounded in the ontological distinctiveness of Imago Dei which encompasses relational covenant with God, intrinsic moral consciousness, and eschatological destiny. While AI hardware functions as an extension of human creativity reflecting the imago Dei, it cannot possess the spiritual-relational essence that constitutes human personhood. The conclusion offers ethical-pastoral guidelines for navigating the tension between technological progress and theological anthropology, emphasizing the necessity of maintaining human moral oversight in autonomous systems.